Difficulté de l'enseignant : à qui appartient-elle ? de quoi parle-t-on ? - Sandra Cadiou
What does the expression « teacher's difficulty » refer to: a difficulty in teaching, a learning difficulty perceived by the teacher or a learning difficulty perceived by the student? We rely on the clinical didactic vignette of Viviane teacher of French and four of his students in vocational high school during a writing sequence (from verbatim courses, interviews semi-directed and texts produced by students). The congruence between the three levels superimposed behind this« teacher's difficulty » is not always present and suggests that it would exceed the strict knowledge and would be connected with the subjects of the situation. With the framework of clinical didactics, considering the Freudian unconscious, we propose to examine the part of transfer in this difficulty. This would help to think of it as a motor of the relationship, explorable in teacher training.